OP0044 The effects of multiple doses of sclerostin antibody AMG 785 in healthy men and postmenopausal women with low bone mass. (23rd January 2014) - Padhi, D.; Allison, M.; Kivitz, A.J.; Gutierrez, M.J.; Stouch, B.; Wang, C.; Jang, G.
Abstract : Background: AMG 785 is a sclerostin antibody (Scl-Ab) that blocks sclerostin from inhibiting osteoblast maturation and function and has been shown to stimulate bone formation. Objectives: Evaluate the pharmacokinetics (PK), pharmacodynamics (PD), and safety of multiple doses of Scl-Ab in healthy men and postmenopausal women with low bone mass. Methods: This double-blind, placebo-controlled, randomized, ascending multiple dose study enrolled healthy men and postmenopausal women aged 45 to 80 years with a lumbar spine or total hip DXA T-score ≤–1.0 and ≥–2.5. Subjects were enrolled into 1 of 6 groups and were then randomized 3:1 to Scl-Ab or placebo. Women received 6 subcutaneous doses of 1 mg/kg or 2 mg/kg Scl-Ab once every 2 weeks (Q2W), or 3 doses of 2 mg/kg or 3 mg/kg Scl-Ab once every 4 weeks (Q4W). Men received 1 mg/kg Scl-Ab Q2W or 3 mg/kg Scl-Ab Q4W. All subjects were instructed to take daily supplements containing calcium and vitamin D. PK, PD, and safety were monitored for up to 24 weeks. Results: Enrolled subjects (36 Scl-Ab, 12 placebo) had a mean age of 59 years and a mean lumbar spine DXA T-score of –1.20 (Scl-Ab) and –1.29 (placebo). Mean serum Scl-Ab exposures were similar in women and men and increased approximately dose-proportionally across the Q2W and Q4W dose ranges. During the treatment period, Scl-Ab caused maximum increases from baseline in PINP of 66% to 147% across cohorts and maximum decreases from baseline in sCTX of 15% to 50% across cohorts. Scl-Ab treatment significantly increased lumbar spine BMD from baseline, reaching a maximum of 7.2% at 18 weeks (Figure). Two subjects tested positive for neutralizing antibodies with no discernable effects on PK, PD, or safety. Adverse event rates were balanced between groups and no significant safety findings were observed. Conclusions: Multiple doses of Scl-Ab significantly increased the bone formation marker PINP, decreased the bone resorption marker sCTX, increased lumbar spine BMD, and were well tolerated in healthy men and postmenopausal women with low bone mass. These data support the continued clinical investigation of sclerostin inhibition as a potential therapeutic strategy for conditions that would benefit from increased bone formation. Acknowledgement: This study was sponsored by Amgen Inc. and UCB Pharma. Disclosure of Interest: D. Padhi Shareholder of: Amgen Inc., Employee of: Amgen Inc., M. Allison: None Declared, A. Kivitz Speakers Bureau: Amgen Inc., M. Gutierrez: None Declared, B. Stouch Shareholder of: Amgen Inc., Employee of: Amgen Inc., C. Wang Shareholder of: Amgen Inc., Employee of: Amgen Inc., G. Jang Shareholder of: Amgen Inc., Employee of: Amgen Inc.